تأثير تنظيم مستوى الماء الأرضي عن طريق (Mole drainage) على الخصائص الفيزيائية للتربة وعلى إنتاجية نبات البطاطا في الساحل السوري - إبراهيم جهاد; أرسلان أويديس; حسين نصر (Latakia University Journal -Biological Sciences Series, 2019)
أظهرت الدراسة التي أجريت على تنظيم مستوى الماء الأرضي في تربة طينية ثقيلة منتشرة في الساحل السوري بطريقة الصرف الأخدودي mole drainage انخفاض الكثافة الظاهرية للتربة فوق المسارات بمقدار 0.14 غ/سم3، وازدياد حجم المسامات الهوائية الأكبر من 10ميكرون بمقدار 7% ، وزيادة معامل التوصيل الهيدروليكي المشبع بمقدار 0.74 م/يوم، وزيادة حجم المسامات التي تحوي ماء قابلاً للامتصاص (0.2-10ميكرون) بمقدار 2.87% مقارنة مع المعاملة غير المصروفة. وأدّت المسارات المصاغة إلى تخفيض مستوى الماء الأرضي وزيادة الشدّ الرطوبي في التربة فوق المسارات ( تجفيف التربة)، رافق ذلك زيادة في الإنتاجية مقدارها 35% في محصول البطاطا صنف سبونتا، كما تم التوصّل إلى أنّ البعد المثالي بين المسارات هو 1.4 م, والمجال المناسب بين المسارات يقع بين0.5-2.2 م. Using mole drainage, this study is carried out to regulate the depth of water table in heavy clay soil prevalent on the Syrian coast. It shows a reduction in the bulk density of soil above the mole drain by (0.14 g/cm3) , an increase of the volume of air space porosity which has a diameter large than 10μm by7%, an increase of the hydraulic conductivity of saturated soil by 0.74 m/d, and an increase of the volume of pores holding available water (0.2-10 μm) by 2.87%, compared with the non-moled treatment. The executed mole drain has reduced the depth of water table and has increased moisture suction of the soil above mole drains (drying soil); this is associated with an increase in potato (var. Sponta) production by 35%. The results demonstrate that the suitable range for mole drain spacing is 0.5-2.2m, and the optimum between mole drains is 1.4m.